Risk factor of urinary incontinence among menopausal women at Babylon city - Humadee, Saadya; abbas, iqbal (Iraqi National Journal of Nursing Specialties, 2012)
Purpose: To identify the risk factors of urinary incontinency for menopausal women.Methodology: A descriptive analytic study was conducted to identify the risk factor for urinary incontinencyand selected non-probability sample (purposive sample) from (200) menopausal women (45-65) who haveurinary incontinence as visitors and caregiver women who attend at Hila surgical teaching hospital during theperiod 1/11/2010-30/3/2011. Questionnaire format used for data collection was designed and constructedafter reviewing related literatures and previous studies and consists of the following variables: Demographicand reproductive characteristics of menopausal women who suffers from urinary incontinenceResults: The study found that the highest percentage was (33.5%, 32%) of study sample their age group (50-54,45-49) years, (74%) they are married and (43.5%) was illiterate. Women in this study had (19%) urgeincontinence, (16.5%) stress incontinence with (38%) having mixed incontinence while (10.5%) mildincontinence with 38.5% having sever incontinence. And the results show that there was statistical significantcorrelation coefficient between type of urinary incontinence and Age at marriage (years), Age at firstpregnancy (years) and parity. There was statistical significant correlation coefficient between degree of urinaryincontinence and age (years), age at marriage, age at first pregnancy (years) and body mass index. There wasstatistical significant correlation coefficient between duration of urinary incontinence with occupation andeconomical status age (years), parity, and number of abortion. The other risk factors include smoking, parity,types of deliveries, previous curettage, previous hysterectomy, Diabetic Mellitus, hypertension disorder,urinary tract infection, coughing, constipation, genital prolapsed and obstructed delivery.